Real-world comparison of major bleeding risk among non-valvular atrial fibrillation patients initiated on apixaban, dabigatran, rivaroxaban, or warfarin - Lip, Gregory Y. H.; Keshishian, Allison; Kamble, Shital; Pan, Xianying; Mardekian, Jack; Horblyuk, Ruslan; Hamilton, Melissa (Thrombosis and Haemostasis, 2016)
In addition to warfarin, there are four non-vitamin K antagonist oral anticoagulants (NOACs) available for stroke prevention in non valvular atrial fibrillation (NVAF). There are limited data on the comparative risks of major bleeding among newly anticoagulated NVAF patients who initiate warfarin, apixaban, dabigatran, or rivaroxaban, when used in ‘real world’ clinical practice. The study used the Truven MarketScan® Commercial & Medicare supplemental US claims database. NVAF patients aged ≥18 years newly prescribed an oral anticoagulant 01JAN2013–31DEC2014, with a ≥1-year baseline period, were included (study period: 01JAN2012–31DEC2014). Major bleeding was defined as bleeding requiring hospitalisation. Propensity score matching (PSM) was used to balance age, sex, region, baseline comorbidities, and comedications. Cox proportional hazards models were used to estimate the PSM hazard ratio (HR) of major bleeding. Among 45,361 newly anticoagulated NVAF patients, 15,461 (34.1 %) initiated warfarin, 7,438 (16.4 %) initiated apixaban, 17,801 (39.2 %) initiated rivaroxaban, and 4,661 (10.3 %) initiated dabigatran. Compared to matched warfarin initiators, apixaban (HR: 0.53; 95 % CI: 0.39–0.71) and dabigatran (HR: 0.69; 95 % CI: 0.50–0.96) initiators had a significantly lower risk of major bleeding. Patients initiating rivaroxaban (HR: 0.98; 95 % CI: 0.83–1.17) had a non-significant difference in major bleeding risk compared to matched warfarin patients. When comparisons were made between NOACs, matched rivaroxaban patients had a significantly higher risk of major bleeding (HR: 1.82; 95 % CI: 1.36–2.43) compared to apixaban patients. The differences for apixaban-dabigatran and dabigatran-rivaroxaban matched cohorts were not statistically significant. Among newly anticoagulated NVAF patients in the real-world setting, apixaban and dabigatran initiation was associated with significantly lower risk of major bleeding compared to warfarin initiation. When compared to apixaban, rivaroxaban initiation was associated with significantly higher risk of major bleeding.Note: The review process for this paper was fully handled by Christian Weber, Editor in Chief.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Non-valvular atrial fibrillation; major bleeding; warfarin; apixaban; dabigatran; rivaroxaban